Risk factors for late reconnections after circumferential pulmonary vein isolation guided by lesion size index – Data from repeat invasive electrophysiology procedure - Mujović, Nebojša M.; Marinković, Milan M.; Marković, Nebojša; Kocijančić, Aleksandar; Kovačević, Vladan; Vučićević, Vera; Mujović, Nataša M.; Potpara, Tatjana S. (Frontiers in Cardiovascular Medicine, 2023)
Background: Late reconnections (LR) of pulmonary veins (PVs) after wide antral circumferential ablation (WACA) using point-to-point radiofrequency (RF) ablation are common. Lesion size index (LSI) is a novel marker of lesion quality proposed by Ensite Precision mapping system, expected to improve PV isolation durability. This study aimed to assess the durability of LSI-guided PVI and the risk factors for LR of PVs. Methods: the prospective study included 33 patients with paroxysmal atrial fibrillation (PAF) who underwent (1) the index LSI-guided WACA procedure (with target LSI of 5.5-6.0 for anterior and 5.0-5.5 for posterior WACA segments) and (2) the 3-month protocol-mandated re-mapping procedure in all patients, irrespective of AF recurrence after the index procedure. Ablation parameters reported by Ensite mapping system were collected retrospectively. The inter-lesion distance (ILD) between all adjacent WACA lesions was calculated off-line. Association between index ablation parameters and the LRs of PVs at 3 months was analyzed. Results: The median patient age was 61 (IQR: 53–64) years and 55% of them were males. At index procedure, the first-pass WACA isolation rate was higher for the left PVs than the right PVs (64% vs 33%, p=0.014). In addition, a low acute reconnection rates were observed, as follows: in 12.1% of patients, in 6.1% of WACA circles, in 3.8% of WACA segments and in 4.5% of PVs. However, the 3-month remapping study revealed LR of PV in 63.6% of patients, 37.9% of WACA circles, 20.5% of WACA segments and 26.5% of PVs. The LRs were identified mostly along the left anterior WACA segment. Independent risk factors for the LR of WACA were left-sided WACA location (OR 3.216 [95%CI: 1.065–9.716], p=0.038) and longer ILD (OR 1.256 [95%CI: 1.035–1.523] for each 1-mm increase, p=0.021). The ILD of >8.0 mm showed a predictive value for the LR of WACA. A single case of cardiac tamponade occurred following the re-mapping invasive procedure. No other complications were encountered.Conclusions: Although the LSI-guided PVI ensures a consistent PVI during the index procedure, LRs of PVs are still common. The PVI durability requires an optimal ILD between adjacent lesions, especially along the anterior lateral ridge.